ИМЕНА-МИФОЛОГЕМЫ В БЕЛОРУССКИХ МАСС-МЕДИА: ПРАГМАСТИЛИСТИЧЕСКИЙ АСПЕКТ - Ратникова, Ирина (Studia Rossica Posnaniensia, 2008)
The author’s attention is focused on Vilna (Vilnius) - one of the toponyms (geographical names) that have acquired the status of cultural concepts and represent an important part of Belarusian national world view, such as The Great Duchy of Lithuania, Grunwald, MenskJMinsk, Kurapaty, Chernobyl, and so on. Vilna is one of the most important Belarusian mythologems which represents the myth about the Golden Age of Belarus. The author does research into the Vilna concept in the field of a cognitive semantic paradigm. Belarusian periodicals, such as Spadchyna, ARCHE, Nasha Niva dated 2000 2005 and the Internet resources, were the source of the linguistic material. The author examines the correlation of Vilna/Jerusalem, Vilna/Mens к, and Vilna/ Vilnius concepts.